Collective bargaining about corporate social responsibility - Laszlo Goerke; Nora Paulus (Canadian Journal of Economics/Revue canadienne d'économique, 2024)
Abstract If a profit-maximizing firm credibly commits to an employment-enhancing corporate social responsibility objective in negotiations with a trade union, the union can reduce its wage demands. Lower wages, ceteris paribus, raise profits, while the increase in employment enhances the payoff of a wage-setting trade union. Therefore, both the firm and the trade union can be better off in the presence of a collectively bargained corporate social responsibility objective than in its absence. Accordingly, establishing a corporate social responsibility objective can give rise to a Pareto improvement and mitigate the inefficiency resulting from collective wage negotiations.
Keywords: 330